Review of the Method of Valuation of the SDR- Amendment to Rule O-1. (Policy Papers; Policy Paper ;, 2022)
This paper seeks Executive Board approval of an amendment to Rule O-1 of the IMF's Rules and Regulations, which specifies the currency amounts in the SDR valuation basket In accordance with Decision No. 17247-(22/44), adopted May 11, 2022, on the method of valuation of the SDR and Decision No. 16033-(16/17), adopted July 20, 2016 on the guidelines for the calculation of currency amounts in the SDR valuation basket, the amounts of each currency included in the SDR valuation basket, effective August 1, 2022, have been determined. These currency amounts are calculated in accordance with long-standing principles of continuity and stability of the SDR value in terms of currencies. The calculations ensure that on the transition day (today), the value of the SDR in U.S. dollars is the same under the new and the prevailing SDR valuation baskets. Moreover, at the average exchange rates for the three-month period ending today (May 2 through July 29, 2022), the share of each currency in the value of the SDR corresponds to the weight approved by the IMF Executive Board on May 11, 2022.